Formation of economic and ecological competences of students in the context of learning the concept of sustainable development in a game form - Shandova, Nataliia; Mieshkova-Kravchenko, Natalia; Oliinyk, Nataliia; Mieshkov, Oleksandr; Radchenko, Kyrylo (Здобутки економіки: перспективи та інновації, 2025)
Today, the ecology issue is relevant and important. Combining the study of environmental and economic aspects in educational institutions in a game format will give a significant result. If we talk about the massive use of such products in education, there are currently no special board games, or they are developed locally. The study purpose is to develop a special software package that is an “Green Economy School” program extension and adapts it to the interactive lesson format. The following methods were used: analysis of literature sources, comparison, and sociological survey on the optimal graphic format, construction of algorithms, three-dimensional modeling. As a results of the work, the economic and environmental board game “Green Adventure”, which is part of the educational and developmental program “School of Green Economy”, was adapted for use in online mode. This was implemented by the Unity software using the C# programming language. The possibility of using the development in distance learning by students of grades 3-5 is a significant difference from existing analogues. The developed vertical slice of the program implements all the key mechanics that allow it to be used for testing in educational institutions. After receiving the results of the testing, we will either continue development and add all the locations of the playing field, or, if students do not like some aspects of the developed complex, we will modify the work of the software complex, depending on the feedback from the players. Conclusions: based on the sociological survey results, the vector graphics was chosen. A 3D-map model of the developed complex prototype was created. The algorithms were realized in the C# programming language. A program prototype was developed, which includes the package basic mechanics. In the Unity, a software package prototype was created for use in the format of an interactive lesson, containing a closed map of the game and several locations that can be improved. In the future, the developed complex will be tested in educational institutions of Kyiv among 3-5 grades students using a special methodology. The testing results will determine the effectiveness of the proposed software package and identify package aspects that need to be redesigned or improved. The results can be applied to digital education programs that promote sustainable development and green economic thinking among primary school students.